Analisa Biaya Operasional Keuangan Usaha Peternakan Sapi Perah Enjang Farm di Kampung Mekarwangi, Kecamatan Cisarua - Cica Cahyati; Neng Maratussolehah; Resa Mustafa Alawiyah; Serli Audista; Yati Nurhayati (Indo Publishing, 2026)
Dairy farming businesses play a crucial role in meeting national milk demand; however, business sustainability is heavily influenced by effective operational cost management. This study aims to analyze financial operational costs, identify dominant cost components, and examine operational cost management practices at Enjang Farm in Kampung Mekarwangi, Cisarua District. A qualitative approach with a descriptive method was employed, utilizing in-depth interviews, observation, and documentation involving the business owner. Data analysis followed the Miles, Huberman, and Saldaña model, comprising data condensation, data display, and conclusion drawing. The results indicate that feed costs constitute the largest component of the cost of goods produced. Meanwhile, financial record-keeping remains rudimentary and cash-flow oriented, failing to implement agricultural accounting principles in accordance with SAK 241. Nevertheless, the business generates net profit, and the available financial information has facilitated operational decision-making. The study demonstrates that adopting more systematic financial record-keeping aligned with agricultural accounting standards could enhance the quality of financial information and support the efficiency and sustainability of the dairy farming business